2017
DOI: 10.1108/imds-11-2016-0471
|View full text |Cite
|
Sign up to set email alerts
|

Use contexts of personal computing devices: determinants of use context changes

Abstract: Purpose The purpose of this paper is to investigate the use contexts of personal computing devices in multiple steps and conducts an in-depth analysis for the use context of smartphones. The determinants of use context changes of smartphones are investigated using the technology-to-performance chain model. Design/methodology/approach In steps 1 and 2, a diary study method and 2014-2015 Korea media panel research data provided by the Korea Information Society Development Institute are used. Correspondence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In researching variables influencing mobile game users’ attitudinal behaviors, Kim et al (2019) found that perceived use-context as environmental and contextual factors had a positive influence on users’ belief, the components of which were perceived application usefulness and perceived ease of use. In particular, temporal, spatial and collaborative factors were found to be influential on users’ perceived usefulness of mobile phone applications (Kim et al ., 2017, 2019). These external variables of use context are expected to be more significant in predicting individuals’ behaviors in ubiquitous computing environments thanks to the development of mobile technology.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In researching variables influencing mobile game users’ attitudinal behaviors, Kim et al (2019) found that perceived use-context as environmental and contextual factors had a positive influence on users’ belief, the components of which were perceived application usefulness and perceived ease of use. In particular, temporal, spatial and collaborative factors were found to be influential on users’ perceived usefulness of mobile phone applications (Kim et al ., 2017, 2019). These external variables of use context are expected to be more significant in predicting individuals’ behaviors in ubiquitous computing environments thanks to the development of mobile technology.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The situation in which a user is currently using Liulishuo is likely to affect the interaction with AI function in the application. This is because interaction with AI possibly happens when the use contexts in which users want to use Liulishuo is appropriate and fit to the user's situation (Kim et al, 2017). Dimmick (2003) claimed that gratification-opportunities are the outcome of the assessment between old and new media and especially it focuses on the flexibility to assign time and other resources for using the media that might be limited by the social situation and the user's location.…”
Section: Use Contextsmentioning
confidence: 99%
“…Goodhue and Thompson did a series of studies on how technologies lead to an individual's performance impact, and they proposed the model of technology-to-performance chain (TPC) [14]. This model draws a sophisticated picture of the way in which technology, user tasks, and utilization are related to changed performance [43]. The TPC combines insight from research on user attitudes, as predictors of utilization, with the concept of task-technology fit (TTF) as a predictor of performance impacts [44].…”
Section: Technology-to-performance Chainmentioning
confidence: 99%
“…Accordingly, various studies have used context-specific factors when they develop theories in IS research (e.g. Hong et al , 2014; Kim et al , 2017; Kim et al , 2019; Kirova and Thanh, 2019). For example, Kim et al (2019) used time, location, social and technological contexts in online game adoption research.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%